The French Wilms' tumour study: no clear evidence for cancer prone families. Issue 6 (June 1994) - Moutou, C; Hochez, J; Chompret, A; Tournade, M F; Le Bihan, C; Zucker, J M; Lemerle, J; Bonaïti-Pellié, C
Abstract : Wilms' tumour of the kidney is known to occur in Beckwith-Wiedemann syndrome. It has also been described in four cancer prone families displaying Li-Fraumeni syndrome but it is not usually considered to be part of this syndrome. In order to detect particular familial cancer aggregations associated with this tumour, we studied the cancer incidence and mortality among relatives of the 501 Wilms' tumour patients in the French Wilms' Tumour Study. We found no familial association with breast cancer or soft tissue sarcomas which are the most common cancers in the Li-Fraumeni syndrome. However, we found two significant familial associations of Wilms' tumour with bone cancers on the one hand and with brain tumours on the other hand. These associations could reflect a small proportion of families segregating for some susceptibility gene. This should then be confirmed at the molecular level.